MMSET regulates histone H4K20 methylation and 53BP1 accumulation at DNA damage sites - Pei, Huadong (2011)
p53-binding protein 1 (53BP1) is known to be an important mediator of the DNA-damage response1, with di-methylation of histone H4 lysine 20 (H4K20me2) critical to the recruitment of 53BP1 to double strand breaks (DSBs)2,3. However, it is not clear how 53BP1 is specifically targeted to the sites of DNA damage, since the overall level of H4K20me2 does not seem to increase following DNA damage. It has been proposed that DNA breaks may cause exposure of methylated H4K20 previously buried within the chromosome, however experimental evidence for such a model is lacking. Here we found that H4K20 methylation actually increases locally upon the induction of DSBs and that methylation of H4K20 at DSBs is mediated by the histone methyltransferase (HMT) MMSET (also known as NSD2 or WHSC1). Downregulation of MMSET significantly decreases H4K20 methylation at DSBs and the subsequent accumulation of 53BP1. We further found that the recruitment of MMSET to DSBs requires the γH2AX-MDC1 pathway, specifically the interaction between the MDC1 BRCT domain and phosphorylated Ser102 of MMSET. Thus, we propose that a pathway involving γH2AX-MDC1-MMSET regulates the induction of H4K20 methylation on histones around DSBs which, in turn, facilitates 53BP1 recruitment.